Green’s function of the convective wave equation for an infinite straight rigid-walled pipe of rectangular cross-section - Borisyuk, A. O. (Reports of the National Academy of Sciences of Ukraine, 2015)
Green's function of the wave equation for an infinite straight rigid pipe of rectangular cross-section with uniform mean flow is found. In this function, the indicated flow effects are reflected in the direct form. The effects become more significant as the flow Mach number increases, by causing, in particular, the appearance and the further growth of a function asymmetry about the cross-section, in which the unit point impulse acoustic source is located. Vice versa, a decrease of the Mach number results in a decrease of the effects and, in particular, in a decrease of the indicated asymmetry.